OP0091 A TWO-SCORE INTERFERON SIGNATURE AND MUSCULOSKELETAL IMAGING EXPLAIN THE ASSOCIATION BETWEEN INTERFERON AND ARTHRITIS IN SLE. (2nd June 2020) - Wigston, Z.; Burska, A.; Alase, A.; Mahmoud, K.; Vital, E.
Abstract : Background: Interferon (IFN) signature is associated with disease activity and flare in SLE. We previously described two independent IFN gene expression scores; IFN Score A (the most commonly measured ISGs) and IFN Score B (less commonly measured ISGs which may also respond to IFN-II or other immune mediators)[1]. Many more clinical outcomes are associated with IFN Score B than with a "classic" interferon signature. These include progression of At-Risk individuals to SLE, response to rituximab, and differentiation of IFN signature in RA and SLE. In previous work, the relationship of IFN Signatures with arthritis was less clear than for other SLE features. This may be related to the local regulatory effects of IFN-beta in the synovium, contrasting with the pro-inflammatory effects of other interferons. Another reason may be the proven imprecision of clinical examination as a measure of MSK inflammation in SLE. USEFUL was a multicentre longitudinal study including serial ultrasound assessment of SLE patients with inflammatory MSK pain receiving treatment with glucocorticoids (GC). Objectives: To determine whether IFN scores A and B are associated with imaging-proven synovitis in SLE and measure the responsiveness of IFN scores to GC treatment. Methods: 133 SLE patients were recruited into the USEFUL study if the referring physician deemed they had inflammatory pain warranting treatment. Participants received depomedrone 120mg IM then were assessed at 0, 2 and 6 weeks using clinical instruments and ultrasound (US). OMERACT US criteria were used to categorise patients as active (GS2 or PD1 in at least one joint or tendon), active in both joints and tendons, or non-active (no GS1 and PD0 or better in all joints). Expression of 26 interferon stimulated genes, normalised to PP1A was measured in whole blood collected in TEMPUS tubes using a custom Taqman array. IFN scores A and B were calculated as previously described[1]. Missing data was imputed using expectation-maximisation method. Parametric tests were applied with post hoc Tukey to compare scores between groups. Results: At baseline, there was no significant difference in IFN Score A between ultrasound groups (F = 1.045, p = 0.355). In contrast, IFN Score B differed significantly between ultrasound groups (F = 4.168, p = 0.018). The greatest difference was between active ultrasound for both joints and tendons (n=22) and non-active ultrasound (n=53) (difference = 0.75, 95% CI 0.13, 1.37, p=0.013). There was no significant change from baseline in IFN Score A at week 2 (mean difference 0.08, 95% -0.14, 0.31, p = 0.45) or week 6 (mean difference -0.03, 95% -0.25, 0.19, p = 0.79). Similarly, there was no significant change in IFN Score B at week 2 (mean difference -0.01, 95% -0.18, 0.17, p = 0.93) or week 6 (mean difference -0.07, 95% -0.21, 0.08, p = 0.36). Conclusion: Previous studies were unable to demonstrate an association between a typical interferon signature and arthritis in SLE. Our study includes a homogenous patient population and therapy, objective measure of synovitis, and a more detailed assessment of IFN Status. We found that imaging-proven synovitis is associated with increased expression of a specific subset of ISGs (IFN score B), but not a the more typical interferon signature genes (IFN Score A). This increases the body of evidence for the value of IFN score B in predicting clinical outcomes. GC treatment did not affect systemic IFN signature scores at follow up. Future analysis will explore the role of IFN Scores in predicting clinical responses to therapy in this study. References: [1]El-Sherbiny, Y.M., et al. Scientific Reports, 2018. 8 (1): p. 5793. Disclosure of Interests: Zoe Wigston: None declared, Agata Burska: None declared, Adewonuola Alase: None declared, Khaled Mahmoud: None declared, Edward Vital Grant/research support from: AstraZeneca, Roche/Genentech, and Sandoz, Consultant of: AstraZeneca, GSK, Roche/Genentech, and Sandoz, Speakers bureau: Becton Dickinson and GSK